Some Early Evidence of Worksharing: Lancashire before 1850 - Huberman, Michael (Business History Review, 1995)
The first generation of enterprises during the industrial revolution had made sizeable investments in new machinery and plant, and to amortise these fixed costs it is widely believed that firms worked long hours, regardless of the state of trade. A detailed study of Lancashire textile firms in 1841 shows this picture to be inaccurate. Short-time working was a common response of firms, especially large ones, during cyclical downturns in the nineteenth century. Firms used collective output cuts as a means to protect the wage lists they had negotiated with workers. The lists also promoted and preserved the regional basis of the industry. As for workers, they saw short-time as a means to protect their jobs and the standard relation between effort and pay. Enforced by sanctions on firms that broke output agreements, short-time evolved into a rule of thumb in the Lancashire textile industry.
_eprint: https://doi.org/10.1080/00076799500000125